Contemporary best practice in the management of malignant pleural effusion. (26th June 2018) - Koegelenberg, Coenraad F.N.; Shaw, Jane A.; Irusen, Elvis M.; Lee, Y. C. Gary
Malignant pleural effusion (MPE) affects more than 1 million people globally. There is a dearth of evidence on the therapeutic approach to MPE, and not surprisingly a high degree of variability in the management thereof. We aimed to provide practicing clinicians with an overview of the current evidence on the management of MPE, preferentially focusing on studies that report patient-related outcomes rather than pleurodesis alone, and to provide guidance on how to approach individual cases. A pleural intervention for MPE will perforce be palliative in nature. A therapeutic thoracentesis provides immediate relief for most. It can be repeated, especially in patients with a slow rate of recurrence and a short anticipated survival. Definitive interventions, individualized according the patient's wishes, performance status, prognosis and other considerations (including the ability of the lung to expand) should be offered to the remainder of patients. Chemical pleurodesis (achieved via intercostal drain or pleuroscopy) and indwelling pleural catheter (IPC) have equal impact on patient-based outcomes, although patients treated with IPC spend less time in hospital and have less need for repeat pleural drainage interventions. Talc slurry via IPC is an attractive recently validated option for patients who do not have a nonexpandable lung.